Initial Business Development of PT CNG with Implementation of the Mutualism Network Strategy (Munets) Model - Wahyudin, Wahyudin; Rifa, Muhammad Rizal; Putra, Candra Galang Gemilang; Debora, Fransisca; Nisah, Firda Ainun (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
The development of a business by a company is determined by the ability to develop strategies. Every company needs to use a strategy to expand its business. Not only large companies but small companies or companies that are going to start a business should also use strategic management. CNG Indonesian Produk is one of many new distribution manufacturing companies working in fashion, food, and agriculture. Brands that are still relatively new can become a fundamental problem, thus hindering the marketing process to be carried out. This study aims to develop appropriate strategies for developing the CNG Indonesian Product business by expanding the company’s network which will have an impact on increasing demand and company productivity. Mutualism Network Strategy (Munets) is the model used in this study. Munets is a marketing strategy that utilizes pre-existing networks and newly formed networks to produce a symbiosis of mutualism that is mutually beneficial for both business owners and parties involved in the network formed. In its application, the increase in sales demand increased 5x compared to before the implementation of Munets. So it can be concluded that the Munets model can expand the company’s partner network which can increase sales demand and produce a mapping of the needs of each company division and strategic application proposals. Of course, it is necessary to control the implementation of the Munets model and the application of other business strategy methods in the development of the Indonesian CNG Product company.